Comparison of single injection and three monthly injections of intravitreal bevacizumab for macular edema associated with branch retinal vein occlusion - Ito Y (Dove Medical Press, 2015)
Yuka Ito, Yoshitsugu Saishin, Osamu Sawada, Masashi Kakinoki, Taichiro Miyake, Tomoko Sawada, Hajime Kawamura, Masahito Ohji Department of Ophthalmology, Shiga University of Medical Science, Otsu, Shiga, Japan Purpose: Our aim was to compare the 1 year efficacy and safety results of intravitreal bevacizumab (IVB) in two prospective, consecutive groups of patients with macular edema (ME) following branch retinal vein occlusion (BRVO).Patients and methods: Twenty-five eyes with ME after BRVO received one IVB injection (single-injection group) and 27 eyes received three monthly IVB injections (three-injection group). Both groups were followed monthly for 12 months. The best-corrected visual acuity (BCVA) and the central foveal thickness (CFT) on optical coherence tomography were evaluated before and after treatment. Patients were eligible to receive an IVB injection if the mean CFT increased 100 µm or more or the BCVA decreased 0.1 logarithm of the minimum angle of resolution (logMAR) unit or more compared with values measured on the last visit.Results: The mean logMAR BCVA and CFT, respectively, improved from 0.56 to 0.33 and from 598 µm to 348 µm in the single-injection group (P<0.001) and from 0.55 to 0.26 and from 514 µm to 293 µm in the three-injection group (P<0.001). During the study period, the mean total number of injections was significantly smaller in the single-injection group than in the three-injection group (2.1 and 4.3, respectively, P<0.001). No serious complications related to the IVB injections developed in either group.Conclusion: The single-injection group achieved similar visual outcomes for ME secondary to BRVO with fewer injections compared with the three-injection group. Keywords: branch retinal vein occlusion, bevacizumab, single intravitreal injection, three monthly intravitreal injections